2020
DOI: 10.3390/su12031218
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Trend of Aging Regions and Their Neighborhood Environment: Findings from Daegu Metropolitan City, Korea

Abstract: This study aims to examine how the aging population of each region has changed from 2009 to 2018, and how age-friendly the current neighborhood environments are in those areas in Daegu, Korea. The 139 administrative units are used as spatial units to identify aging regions, while 100 m × 100 m grid cells are employed as spatial units to capture the environmental variables of the neighborhood comprehensively. To analyze Daegu’s aging regions, emerging hotspot analysis was performed, demonstrating the spatio-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(82 reference statements)
0
5
0
1
Order By: Relevance
“…In particular, the free ride program for senior citizens aged 65 or older in Korea makes them likely to choose alternative transportation instead of personnel driving. In this study, older adults living in six residential areas with metros may have easily chosen to stop driving because of the high accessibility, convenience, and low cost of public transportation [ 31 , 32 ]. One study reported that older drivers in rural areas were driving longer than those in urban areas because of limited transportation support [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the free ride program for senior citizens aged 65 or older in Korea makes them likely to choose alternative transportation instead of personnel driving. In this study, older adults living in six residential areas with metros may have easily chosen to stop driving because of the high accessibility, convenience, and low cost of public transportation [ 31 , 32 ]. One study reported that older drivers in rural areas were driving longer than those in urban areas because of limited transportation support [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pentingnya pendidikan terkait topik kelanjutusiaan bagi masyarakat umum dan tenaga kesehatan diketahui dapat meningkatkan pemahaman dan cara pandang yang lebih positif dalam rekognisi terhadap penuaan yang sehat (E. J. Kim, Kim, & Kim, 2020). Selain itu, sosialisasi konsep menua bagi masyarakat dapat berimplikasi positif terhadap kebutuhan lansia akan proteksi sosial dan akses terhadap pelayanan kesehatan (United Nations, 2019).…”
Section: Gambarunclassified
“…The shrinking and aging of the Japanese population, coupled with continuous polarization effects towards urban centers, have led to a clear dissolution of the countryside [55,56]. Population problems in the countries near Japan are the same [57], as shown by Hwang et al [58]. Lastly, extraversion has played a moderating role in the relationship between suitable behavior and activity involvement.…”
Section: Exhibitions and Populationmentioning
confidence: 99%